Composite honeycomb core sandwich plate with facesheet indentation model subjected to low-velocity impact - Drahman, Siti Hasyyati (2015)
The composite sandwich structures are applied in many engineering fields due to their high strength and stiffness but lightweight properties. The purpose of this study is to obtain the top facesheet indentation and strain failure of a fixed-end composite sandwich plate with honeycomb core when it is subjected to low-velocity impact by using MATLAB software. The faceheets are made from Hercules AW193-PW prepreg consisting of AS4 fibers in a 3501-6 matrix (carbon/epoxy) with fiber orientation of [0/90]. The honeycomb core is made from HRH 10 1/8-3.0 Nomex honeycomb (Ciba-Geigy). Type of the impactor used in this study is flat-ended cylinder, which is made from case-hardened steel. The composite sandwich plate is modeled as a two-dimensional problem with five and three degree-of-freedom per node for the facesheets and honeycomb core, respectively. Only the stiffness matrix, [ ], and the mass matrix, [ ], are considered in determining the responses of the plate. The force is applied at the center of the plate only. Responses in terms of indentation, strain failure and displacement are explored. It was found that the most efficient stacking sequence of facesheet is [±45]. Also, the most effective parameter in improving the strain failure of the top facesheet is crushing resistance of the core.